Flavonoid 4'-O-Methylkuwanon E from Morus alba Induces the Differentiation of THP-1 Human Leukemia Cells - Kollar, Peter; Bárta, Tomáš; Keltošová, Stanislava; Trnová, Pavlína; Müller Závalová, Veronika; Šmejkal, Karel; Hošek, Jan; Fedr, Radek; Souček, Karel; Hampl, Aleš (Evidence-based complementary and alternative medicine, 2015)
Aims. In this work we studied cytodifferentiation effects of newly characterized prenyl flavonoid 4'-O-methylkuwanon E (4ME) isolated from white mulberry (Morus alba L.). Main Methods. Cell growth and viability were measured by dye exclusion assay; cell cycle and surface antigen CD11b were monitored by flow cytometry. For the cytodifferentiation of cells the NBT reduction assay was employed. Regulatory proteins were assessed by western blotting. Key Findings. 4ME induced dose-dependent growth inhibition of THP-1 cells, which was not accompanied by toxic effect. Inhibition of cells proliferation caused by 4ME was associated with the accumulation in G1 phase and with downregulation of hyperphosphorylated pRb. Treatment with 4ME led to significant induction of NBT-reducing activity of PMA stimulated THP-1 cells and upregulation expression of differentiation-associated surface antigen CD11b. Our results suggest that monocytic differentiation induced by 4ME is connected with up-regulation of p38 kinase activity. Significance. Our study provides the first evidence that 4ME induces the differentiation of THP-1 human monocytic leukemia cells and thus is a potential cytodifferentiating anticancer agent.